A Survey of Routing Protocols and Security Issues in MANET - Sumathi, K; Vimal Kumar, D (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad-hoc network (MANET) is a type of ad hoc network that can change locations and configure itself on the fly and wireless communications. The mobile nodes communicate with each node without any centralized manner. The MANETs does not have any pre-defined network topology. The MANET node wants to send the data between two nodes to establish wireless connection to exchange the data. After data sending is finished the connection is ended. The mobile network topology is regularly changing the location due to nodes moving, resource limitation and bandwidth limitation of mobile node. There are many types of routing protocol available in MANET. In this paper, we discuss about different type of existing MANET routing protocols and its security problems. The MANET routing protocols offered for secure packets sending and face some common attack in ad hoc networks. The routing protocol are subjected to situation against the most frequently identified attack sink hole, grey hole, spoofing, black hole attack and wormhole attack etc. A survey of various issues in MANET regarding security is done considering all major aspects.